The APPSMO Advantage Strategic Opportunities: Evolving Defence Diplomacy with the Asia Pacific Programme for Senior Military Officers - Ong, Keng Yong; Mushahid Ali; Chin, Bernard (World Scientific, 2016)
APPSMO is a series of conferences organised by the S. Rajaratnam School of International Studies and its predecessor, the Institute of Defence and Strategic Studies, for senior military officers of Singapore and other countries of the Asia Pacific, consisting of an intensive week-long programme of lectures, forums, and discussion groups.